Evaluasi Ketersediaan Fasilitas Pada Ruang Terbuka Hijau Perkotaan, Studi Kasus Taman Ratu Balqis di Kabupaten Nagan Raya - Jihan Sasmita Reza; Meutia Meutia; Fitriyani Insanuri Qismullah (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Urban green open spaces play a vital role in city planning, offering a range of ecological, social, and economic benefits. This research evaluates the availability of facilities at Ratu Balqis Park in Nagan Raya Regency, in accordance with the Minister of Public Works Regulation Number 05/PRT/M/2008 on Guidelines for Providing and Utilizing Green Open Space. This study employs a descriptive qualitative method, utilizing primary data gathered through observation and secondary data gathered from literature reviews. The analysis reveals that the park's facilities are inadequate.